Enantiomeric Recognition and Separation by Chiral Nanoparticles - Gogoi, Ankur (Molecules, 2019)
Chiral molecules are stereoselective with regard to specific biological functions. Enantiomers differ considerably in their physiological reactions with the human body. Safeguarding the quality and safety of drugs requires an efficient analytical platform by which to selectively probe chiral compounds to ensure the extraction of single enantiomers. Asymmetric synthesis is a mature approach to the production of single enantiomers; however, it is poorly suited to mass production and allows for only specific enantioselective reactions. Furthermore, it is too expensive and time-consuming for the evaluation of therapeutic drugs in the early stages of development. These limitations have prompted the development of surface-modified nanoparticles using amino acids, chiral organic ligands, or functional groups as chiral selectors applicable to a racemic mixture of chiral molecules. The fact that these combinations can be optimized in terms of sensitivity, specificity, and enantioselectivity makes them ideal for enantiomeric recognition and separation. In chiral resolution, molecules bond selectively to particle surfaces according to homochiral interactions, whereupon an enantiopure compound is extracted from the solution through a simple filtration process. In this review article, we discuss the fabrication of chiral nanoparticles and look at the ways their distinctive surface properties have been adopted in enantiomeric recognition and separation.